Arbitration in swaps: the Portuguese experience. (12th March 2016) - Costa e Silva, Paula; Henriques, Duarte G
Abstract: Until very recently the swaps industry seemed to be reluctant to use arbitration or at least was very indifferent as to this mechanism, with disputes almost always being left for the courts of either London or New York to decide. Indeed, these two jurisdictions have been providing a substantial level of quality and speed in resolving disputes. This scenario has been changing over the past few years, and arbitration is now becoming increasingly common in financial and banking transactions, the swaps and derivatives included. Notwithstanding the (small) dimension of the market, the Portuguese case law shows now a considerable and interesting number of cases decided by the courts in swap related matters. In fact, this experience shows that the use of arbitration not only is practicable, but it is also a good option to resolve disputes in the swaps context. Not only are issues of enforcement of the arbitration agreement at stake but, more importantly, intricate questions regarding the notion of "unexpected change in circumstances" (giving rise to the doctrine of "hardship"), the validity of a swap agreement under the doctrines of "gaming or wagering" (" jeu et pari ") contracts and, lastly, but not less importantly, the (possible) violation of Portuguese public policy. This note addresses the landscape of swap related disputes and the use of arbitration in this context.